Variations in Event‐Bed Thickness‐Frequency Distributions Near Volcanic Islands: Indicators of Varied Geological Processes - Yu‐Chun Chang; José C. F. Kling; Julie C. Schindlbeck‐Belo; Neil C. Mitchell; Kan‐Hsi Hsiung; Toshiya Kanamatsu (Geochemistry, Geophysics, Geosystems)
Abstract A variety of subaerial and submarine events, including mass‐wasting and volcanism, can generate sediment gravity flows and fallout deposits that are preserved in deep‐water stratigraphic records. This study examines whether event beds with differing depositional and transport histories exhibit distinct thickness‐frequency distributions. Analyzing over 4,500 event beds from seven drilling sites near Montserrat, the Izu Arc, the Kyushu‐Palau Ridge, and Gran Canaria, the analyses explore variations in event‐bed characteristics across different climatic periods, volcanic stages, and geomorphological settings. Statistical methods include characterizing thickness‐frequency distributions and assessing subset similarity using t‐tests and smoothed distribution patterns. The data‐driven results indicate discernible differences where dominant geological processes vary. For example, volcanic growth stages at the Kyushu–Palau Ridge produced thicker, coarser, and more frequent event beds compared with quiescent stages. Similarly, beds from the north slope of Gran Canaria—where submarine canyons enhanced sediment delivery—were nearly twice as thick as those from the south. In contrast, indistinguishable characteristics between the rear and frontal Izu Arc subsets after 3 Ma are attributed to the development of an extensional zone supplying material to both arc sides. Comparable distributions were also observed within intervals with minimal geological differences. The reliability of this analytical approach depends on high‐quality sediment recovery, as drilling‐related disturbances may obscure primary depositional signals. Beyond stratigraphic characterization, the method shows broader potential for identifying the provenance of volcanic glass shards through geochemical comparisons and for evaluating the statistical compatibility of data sets from neighboring sites, ensuring sufficient sample size for robust integrated analyses.